Is familial papillary thyroid microcarcinoma more aggressive than sporadic form? - Lee, Cho Rok; Park, Seulkee; Kang, Sang-Wook; Lee, Jandee; Jeong, Jong Ju; Nam, Kee-Hyun; Chung, Woong Youn; Park, Cheong Soo (Annals of surgical treatment and research, 2017)
With the increasing incidence of papillary thyroid microcarcinoma (PTMC), familial papillary thyroid microcarcinoma (FPTMC) is now recognized more frequently. However, the biological behavior of FPTMC is poorly understood. The aim of this study was to investigate the prevalence of FPTMC and its biological aggressiveness. Between March 2006 and July 2010, 2,414 patients underwent primary surgical therapy for PTMC and 149 (6.2%) were further classified as FPTMC. To determine the biological aggressiveness of FPTMC, we compared the clinicopathological features and prognosis between FPTMC and sporadic PTMC (SPTMC). The male-to-female ratio was higher in FPTMC than in sporadic papillary thyroid microcarcinoma (SPTMC: 1:4.5 . 1:7.2, P = 0.041). The central lymph node (LN) metastasis rate was significantly higher in FPTMC than in SPTMC (36.2% . 24.2%, P = 0.002). The local recurrence rate was also higher in FPTMC than in SPTMC (4.5% . 0.6%, P < 0.001). We identified familial occurrence in 6.2% of cases of PTMC. FPTMC is associated with a high rate of central LN metastasis and local recurrence. These findings suggest that close follow-up can be beneficial in FPTMC patients to detect local recurrence.